Why Should We Care about Care? : The Role of Childcare and Eldercare in Serbia - Levin, Victoria (World Bank, Washington, DC, 2018)
Despite a slight increase in female labor participation between 2012 and 2013, employment rates in Serbia stood at 40.1 percent for women in 2013, almost 15 percentage points below employment rates for men (at 54.9 percent). International evidence shows that support for childcare and eldercare affects women’s labor market participation. This note examines the care needs of families with children and or elderly household members and the provision of formal care services in Serbia with an emphasis on the availability, price, and quality characteristics. Based on the analysis of an independent mixed-methods dataset collected in the Western Balkans region, this note documents the perceptions and barriers in the use of quality formal care in Serbia. Quality provision of formal eldercare can potentially improve health outcomes for the elderly through prevention, early detection, and consistent maintenance of chronic diseases, which may imply long-term cost savings in the healthcare sector.